Paraglacial transformation and ice-dammed lake dynamics in a high Arctic glacier foreland, Gåsbreen, Svalbard - Dudek, Justyna; Wieczorek, Iwo; Suwiński, Mateusz K.; Strzelecki, Mateusz C. (Wiley, 2023)
The structural change of the Svalbard landscape from glacially dominated to paraglacial, that has taken place since the termination of the Little Ice Age (ca. 1900) is expressed by the widespread retreat of glaciers and progressive exposure of glacial landforms. This study provides insights into the rate of post-LIA deglaciation and associated paraglacial transformation in the foreland of Gåsbreen, one of the first ever investigated glacier systems in the Arctic. Glacier is situated in Sørkapp Land (Southern Spitsbergen), a region characterized by one of the fastest deglaciation rates in the entire Svalbard Archipelago. During the investigated period, 1938–2020, the Gåsbreen was in a recession that accelerated after 1990, leading to its foreland increasing from 2.2 to 5.8 km2. The dynamics of landscape change in the glacier foreland, exposed since the end of LIA, manifested in i.e. the formation of ice-dammed lakes, degradation in the surface of ice-cored moraines and the landforms that are underlain by dead-ice. Mass movements and debris flow on ice-cored moraines and fluvioglacial processes had a great influence on this transformation. Enhanced proglacial runoff intensified denudation, transport and accumulation of sediments, which resulted, in: an increase in the extent of sandurs and proglacial riverbeds, an increase in the area of glacial lakes, extending and changing of the course of rivers in the glacier foreland. At the same time, the major lake system in the area—Goësvatnet underwent several cycles of filling and draining, often through glacial outburst flooding events.
Keywords: Arctic; glacial lakes; glacial landforms; glacier retreat; paraglaciation; Svalbard